On Weights and Measures: Informational Constraints in Social Welfare Analysis - Sen, Amartya (Econometrica, 1977)
[Regularity conditions in social welfare analysis can be seen as ways of making specific types of information "inadmissible" in welfare judgements: the evaluation is made invariant with respect to information of those types. In this sense, these conditions–often reflecting "principles" of judgement–serve also as informational constraints. In this lecture alternative approaches to social welfare evaluation are examined in this light. The analysis covers both Arrovian and Bergson–Samualsonian social welfare functions as well as principles underlying utilitarianism, Rawlsian conception of justice, notions of liberty and egality, and "historical" theories of rights and entitlements (e.g., Marx or Nozick).]